No evidence that HPV vaccination leads to sexual risk compensation. Issue 6 (2nd June 2016) - Hansen, Bo T.
ABSTRACT: Uptake of the HPV vaccine has been lower than the uptake of most other childhood vaccines offered in public programs. Since the HPV vaccine protects against a sexually transmitted virus, one barrier to uptake specific to the HPV vaccine may be the concern that vaccination may encourage risky sexual behaviour. Unanimous findings from recent studies show that HPV vaccination does not lead to sexual risk compensation, which is an important message to parents, clinicians and other decision-makers regarding HPV vaccination. Some issues remain to be investigated, like HPV vaccination and sexual risk compensation among boys.